Curricularization of Extension through the Development of Computational Solutions Supporting the Sustainable Development Goals - Tives, Heloise Acco; Ancini, Gabriel; Canedo, Edna Dias; Marini, Andreia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3489, 2024)
This work presents an experience report on the Community Projects II course, which focuses on integrating institutional outreach activities into the curriculum. Aimed at contributing to society and the Sustainable Development Goals (SDGs), the class developed five computational solutions during the 2023.2 semester. Interaction with the external community enhanced students’ empathy and understanding of social needs. The course combined classroom instruction for project guidance and analysis with practical activities for solution development. Agile methods SDGs and bi-weekly sprints were employed, allowing students to assess the value generated and make necessary adjustments for subsequent development stages.